Feminist Digital Research Methodology for Rhetoricians of Health and Medicine - De Hertogh, Lori Beth (Journal of Business and Technical Communication, 2018)
This article argues that rhetoricians of health and medicine can benefit from new methodological orientations that more fully account for conducting digital research within vulnerable online communities. More specifically, this article introduces a feminist digital research methodology, an intersectional methodology that helps rhetoricians of health and medicine contend with the overlapping rhetorical, technological, and ethical frameworks affecting how we understand and collect health information, particularly within vulnerable online communities. The author considers methodological shifts in Internet research ethics, rhetorics of health and medicine, and feminist rhetorics as well as definitions and conceptions of online communities and vulnerability. The author next draws from a 5-year case study of an online childbirth community to demonstrate how a feminist digital research methodology offers an alternative methodological orientation that helps researchers navigate ethical decision-making practices that arise from conducting health research within vulnerable online communities. Finally, the author outlines the broader implications of this methodology by suggesting three ways that scholars can use it within and beyond the field.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDUwNjUxOTE4NzgwMTg4